2018
DOI: 10.22271/ortho.2018.v4.i4b.16
|View full text |Cite
|
Sign up to set email alerts
|

AO type C distal femur fracture: results of operative management in 52 patients

Abstract: Background: Intraarticular distal femur fractures are severe injuries posses many challenges in management and associated large number of complications like infection, knee stiffness, delayed union, nonunion, instability, and post-traumatic arthritis. The advent of distal femur locking plate has improved the operative outcome of these fractures. Aim and Objectives: This retrospective study aimed to determine the functional, clinical and radiological outcome of AO type C distal femur fractures treated with dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…22 There are case reports of Hoffa's fracture being treated with a swashbuckler approach. 4 The study revealed that using the Swashbuckler approach doesn't increase the chance of nonunion. The rates of complications were also similar.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…22 There are case reports of Hoffa's fracture being treated with a swashbuckler approach. 4 The study revealed that using the Swashbuckler approach doesn't increase the chance of nonunion. The rates of complications were also similar.…”
Section: Discussionmentioning
confidence: 97%
“…The rates of complications were also similar. 4,22 Ahire et al compared the current approach with the lateral approach in the treatment of the distal femur fractures with 30 patients in each group. The patients were followed up for 1 year wherein the author noticed union in all cases but the lateral approach group was seen to have more major complications and significantly lesser functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation